Analisis Semiotika pada Music Video Jkt 48 dengan Judul Benang Sari, Putik dan Kupu-Kupu Malam - Sari, Sri Indah; Ananda, Rizki Ayu; Sazali, Hasan; Dalimunthe, Maulana Andinata (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research focuses on semiotic analysis of music videos which are the pros and cons in society. The music video for JKT 48 is entitled "Stamen and Night Butterflies". The method used in this study is a qualitative method, which includes: ideas, descriptions of meanings, definitions, characteristics, metaphors, symbols, and others. Based on the author's observations and analysis, in the music video there are scenes that are not in accordance with the culture of our country, namely those that lead to LGBT and are inappropriate for viewing by minors. And using the concept of queerbaiting which refers to and implies heterosexual/LGBT relationships because it uses talent that is entirely female. Keywords: music, symbols, video